In-operando characterizations of oligothiophene OFETs: controlling the structure-property relationships at the nanoscale - Souren Grigorian; Anton Davydok; Linda Grodd; Yuriy Luponosov; Sergey Ponomarenko; Ilaria Fratoddi (Discover Nano)
Abstract Grazing Incident Wide Angle X-ray Scattering (GIWAXS) studies on organic field-effect transistors (OFETs) fabricated with an aliphatic functionalized α,α'-quinquethiophene (i.e. 5,5′′′′-dihexyl-2,2′:5′,2′′:5′′,2′′′:5′′′,2′′′′-quinquethiophene, DH5T) thin film, were carried out. The structure-property relationships of the semiconductor material were investigated. A detailed, spatially resolved microstructural characterization of the active layer was carried out with the aim of understanding the role of the film’s microstructure on electrical performance. For this purpose, a custom-made setup designed for in-operando tests of OFETs was used, allowing a correlation under measured conditions of the complex microstructure with the thin film electrical behavior, under operating conditions. The GIWAXS measurements revealed a significant anisotropy of the DH5T thin films, under source-drain applied voltages (Vsd). Particularly notable variations were observed for both in-plane and out-of-plane directions. Upon applying the Vsd, the microstructure remained relatively stable in the out-of-plane (001) direction, suggesting that this orientation is less affected by the applied voltages. However, in the in-plane (020) direction, an increase of the π–π stacking of the DH5T molecules was found, indicating a stronger response of the microstructure to the applied voltage. Notably, a higher tensile strain, exceeding 1%, was observed at a Vsd of − 10 V, suggesting that the application of voltage induces significant structural reorganization in the thin film, which may have implications for optimizing the performance of OFETs in practical applications.